Roadside use of native plants (Island Press, 2000)
The book opens with eighteen short essays on principles of ecological restoration and management from leading experts in the field including Reed F. Noss, J. Baird Callicott, Peggy Olwell, and Evelyn Howell. Following that is the heart of the book, more than 500 pages of comprehensive state-by-state listings that offer: - a colour map for each state with natural vegetations zones clearly marked - comprehensive lists of native plants, broken down by type of plant (grasses, forbs, trees, etc.) and including both scientific and common names, with each list having been verified for completeness and accuracy by the state's natural heritage program - contact names, addresses, and phone numbers for obtaining current information on invasive and noxious species to be avoided - resources for more information, including contact names and addresses for local experts in each state.